Machine learning with PyTorch and Scikit-Learn : develop machine learning and deep learning models with Python /: develop machine learning and deep learning models with Python. (2022) - Raschka, Sebastian; Liu, Yuxi; Mirjalili, Vahid; Dzhulgakov, Dmytro
No abstract available